Ilações sobre o ajustamento da metodologia de compensação tributária da Lei Kandir - Lemos, Thaisa Oliveira (2018)
OneofthestrategiestotrytoreducetheexternalvulnerabilityoftheBrazilianeconomyistokeepthe balance of trade transactions in surplus, soencouragingexportsandincreasingdomesticinvestmentscanalleviatethisvulnerability as well as increasenationalproduction. Underthesupportofthisargument, Complementary Law (LC) nº 87 ofSeptember 13, 1996, known as the "Kandir Law", wasenacted. Accordingtoher, thestatesgiveupthe ICMS andreceivetransfersfromthe Union tocompensate for the nonpaymentofthistax. In thissense, the overall objectiveofthestudywastoevaluatewhetherthe Kandir Law redistributes in a balancedwaythe financial compensationofthe Union, andhow it corroboratesorinfluencestheexportprocess in theBrazilianstates. The specificobjectives are to: i) estimatetheeffectiveparticipationofeachfederatedentity in Brazilianexports, and compare it withthe individual participationcoefficientsestablished in LC 87/96 between 2000 and 2016; ii) tocalculatethe financial gainsorlossesaccruedaccordingtothe Law between 2000 and 2016, ifthe UF receivedonlendings in proportiontowhattheyactuallyexported; iii) toidentifyhowmuchthevalues ofthelossesorgains, represent in front ofthe total taxes collectedbyeachstateandhowmuchtheyrepresentofthe total transfersthatthe Union makestothestates; iv) toverifylossesandgainsofthefederatedunits, takingintoaccountthe sum ofthespecifictransfers for exportpromotion (Lei Kandir, ExportPromotionFund (FEX and IPI exports). The justification for thiswork lies in theidentificationofthedistortionsofcompensation in relationtothecapacitytocontributetothestabilityoftheBrazilian trade balance in the face oftheneedtocreate a more equitableandefficientmechanismfromanallocative point ofview in relationtothecompensation quota. The hypothesisisthatthecompensationmethodologyoftheshareholderismisleadingwhengenerating a groupofunitsofthefederationthatreceivecompensationabovetheirproducerandexportereffortand anothergroupincurs net lossesfromthecompensation in relationtotheircontributionshare in theexporteffort. For theelaborationofthisresearch, thehypothetical-deductive approach wasusedtogetherwiththehistorical, comparativeandstatistical procedures, basedontheanalysisofsecondary data thatwillbeobtainedthroughtheNationalCouncilofFinancePolicy (CONFAZ) andAnalysis System oftheForeign Trade Information (ALICEWEB) ofthe MDIC (MinistryofDevelopment, Industryand Trade). The resultsshowedthatthere are distortions in therewardofeachfederativeunit in relationtotheexporteffort, andthatthere are statesthataccumulatedlosseswhileothersaccumulatedgainsaccordingtotheproposedmethodolog y.